Problematika Sistem Informasi Manajemen Pendidikan Dengan Aplikasi SIKUAD di SMK Negeri 2 Purwodadi - Lisnanto, Suko; Wahyuningsih , Siti; Sulianto, Joko (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to identify and analyze the problems encountered in the implementation of the Education Management Information System through the SIKUAD application at SMK Negeri 2 Purwodadi. The novelty of this research lies in its in-depth empirical case study focusing on the challenges of implementing SIKUAD, an internally developed integrated academic information system designed by the school. SIKUAD was created to facilitate the management of educational data such as student records, teacher information, class schedules, and other school administration tasks. However, in practice, its implementation is fraught with various technical and non-technical challenges. This research adopts a descriptive qualitative method with data collected through observation, interviews, and documentation. Informants include education personnel, teachers, and school operators directly involved in the use of the SIKUAD application. The findings reveal several key issues, including users’ limited competence in operating the system, lack of technical training, inadequate ICT infrastructure, and difficulties in data integration. Additionally, system reliability issues were found, especially during simultaneous data access, causing disruptions. The study concludes that to ensure the optimal implementation of SIKUAD in supporting education management at SMK Negeri 2 Purwodadi, it is essential to enhance human resource competencies, provide sufficient infrastructure support, and improve the system's technical functionality.